ANALISIS PEMETAAN POTENSI RAWAN PANGAN DAN ARAH KEBIJAKAN (Studi Kasus pada Jabung Kabupaten Malang) - Siti Muslihah; Sugeng Hadi Utomo; Hadi Sumarsono (Universitas Negeri Malang, 2014)
Food is represent requirement of most elementary human being in experiencing their life, so that food can be conceived of rights of human life. Relate at result of mapping by Bappeda Sub-Province of Malang (2007) and result of Mapping of food gristle area, district of Jabung become priority in handling of food gristle area. District of Jabung is district owning physical facility and non physical most minim. Therefore, according to researcher need the existence of relevant study about food gristle potency and also local characteristic and policy direction in improving food resilience District of Jabung Malang Sub-Province. The Result of this research mapping of food gristle potency by using 12 indicators in District of Jabung have not village which enter priority handling of very area gristle, gristle and rather gristle. But that way in analysis each of indicator of course thera are still rather area of gristle, gristle or even very gristle. Policy direction of which can do is maximizing area potency district of Jabung either from facilities and basic facilities aspect and also the make-up of agricultural produce. Keywords: Gristle Food Potency, Policy Direction